2018
DOI: 10.3390/w10091148
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Prediction Method Based on IGRA and LSTM

Abstract: Water quality prediction has great significance for water environment protection. A water quality prediction method based on the Improved Grey Relational Analysis (IGRA) algorithm and a Long-Short Term Memory (LSTM) neural network is proposed in this paper. Firstly, considering the multivariate correlation of water quality information, IGRA, in terms of similarity and proximity, is proposed to make feature selection for water quality information. Secondly, considering the time sequence of water quality informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…Thus, the recent development of these high technologies regarding field monitoring, data transmission, and analyses promotes the optimization of water quality management. However, many parts of water quality monitoring systems still rely on regular-basis manual sample collection and monitoring even though the collected data are analyzed by novel machine learning techniques [16,134,137,140]. Thus, it is essential to develop and apply in situ real-time monitoring systems using sensor technologies, along with high-tech data analysis techniques, such as deep learning, to find better solutions in water quality management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the recent development of these high technologies regarding field monitoring, data transmission, and analyses promotes the optimization of water quality management. However, many parts of water quality monitoring systems still rely on regular-basis manual sample collection and monitoring even though the collected data are analyzed by novel machine learning techniques [16,134,137,140]. Thus, it is essential to develop and apply in situ real-time monitoring systems using sensor technologies, along with high-tech data analysis techniques, such as deep learning, to find better solutions in water quality management.…”
Section: Discussionmentioning
confidence: 99%
“…However, this type possesses a more complex structure than RNNs for controlling the use of the previous memory in recurrent loops [149]. The LSTMs are increasingly employed in the analysis of water quality data sequencing [16,18,150]. Muharemi et al (2019) used various machine learning models (e.g., ANNs, SVMs, and LSTMs) for the analysis of time series data and suggested machine learning for the detection of anomalies in the water quality [142].…”
Section: Advanced Data Analysis With Machine Learning For Water Qualimentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriately chosen evaluation criteria are essential for assessing model performance. Because Krause has found that no single efficiency criterion can provide a full description of model performance [4] and each available criterion has certain benefits and drawbacks, we chose to apply two criteria: the MAE and the RMSE [6].…”
Section: Model Evaluation Criteriamentioning
confidence: 99%
“…These networks have been successfully applied in the field of water time series prediction. For example, Jian Zhou used an LSTM network to predict dissolved oxygen [6] and Chen Liang used an LSTM network to predict the Dongting Lake water level variation [7]. However, the prediction accuracy of the LSTM algorithm used in these studies is influenced by the parameter selection.…”
Section: Introductionmentioning
confidence: 99%